Participatory Use of a Tool to Assess Governance for Sustainable Landscapes - Peteru, Swetha; Duchelle, Amy E.; Stickler, Claudia; Durbin, Joanna; Luque, Cecilia; Komalasari, Mella (Frontiers in Forests and Global Change, 2021)
Sustainable management of resources is crucial for balancing competing livelihood, economic, and environmental goals. Since forests and other systems do not exist in isolation, comprehensive jurisdictional approaches to forest and land-use governance can help promote sustainability. The ability of jurisdictions to provide evidence of progress towards sustainability is essential for attracting public and private sector investments and maintaining local stakeholder involvement. The Sustainable Landscapes Rating Tool (SLRT) provides a way to assess enabling conditions for jurisdictional sustainability through an evidence-based rating system. We applied this rating tool in 19 states and provinces across six countries (Brazil, Ecuador, Indonesia, Cote d’Ivoire, Mexico, Peru) that are members of the Governors’ Climate and Forests Task Force (GCF TF). Each SLRT assessment was completed using publicly available information, interviews with stakeholders in the jurisdiction, and a multi-stakeholder workshop to validate the indicator ratings. This paper explores the effects of stakeholder involvement in the validation process, along with stakeholder perceptions of the tool’s usefulness. Our analysis shows that the validation workshops often led to modifications of the indicator ratings, even for indicators originally assessed using publicly available data, highlighting the gap between existence of a policy and its implementation. Also, a more diverse composition of stakeholders at the workshops led to more changes in indicator ratings, which indicates the importance of including different perspectives in compiling and validating the assessments. Overall, most participants agreed that the tool is useful for self-assessment of the jurisdiction and to address coordination gaps. Further, the validation workshops provided a space for discussions across government agencies, civil society organizations (CSOs), producer organizations, indigenous peoples and local community representatives, and researchers about improving policy and governance conditions. Our findings from the analysis of a participatory approach to collecting and validating data can be used to inform future research on environmental governance and sustainability.